KAJIAN STATUS KERUSAKAN LAHAN UNTUK PRODUKSI BIOMASSA DI KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA - Zulkarnain Zulkarnain (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The objectives of the study of land degradation status for biomass production are: (1) to collect data and information on initial soil conditions on land use for biomass production; (2) to determine land damage status for biomass production on land use for biomass production; and (3) mapping the status of land damage in Marangkayu sub-District, Kutai Kartanegara Regency.The research was carried out for 4 months, the research location was in Semangkok and Sebuntal Villages, Marang Kayu sub District, Kutai Kartanegara Regency. Research activities carried out include: preparation, field observations, soil sampling, soil sample preparation, soil analysis in the laboratory, data processing, and interpretation, and reporting. The results showed that: (1) Land with undamaged status was found in wetlands at Semangkok 4 location; (2) Dry land with mild damage status occurred at Semangkok 5, Semangkok 6, Sebuntal 5, and Sebuntal 6 locations, while wetlands with mild damage status occurred at Semangkok 1, Semangkok 2, Semangkok 3, Sebuntal 1 and Sebuntal 2 locations; (3) Wetlands with moderate damage occurred at Sebuntal 3 and Sebuntal 4 locations, not dry lands with moderate and heavy damage; and (4) Land damage for biomass production mostly occurs in dry land caused by damage to the basic properties of the soil which includes soil erosion, fraction composition, and soil pH, while in wetlands that are damaged with damaged soil properties are soil pH. and the depth of the pyrite layer.